Formulation and implementation of an integer programming model for the course timetabling problem: a case study in Ecuador: Formulación e implementación de un modelo de programación entera para la creación de horarios de clases: un caso de estudio en Ecuador - Saltos Atiencia, Ramiro (2021)
Based on the optimization model proposed by Saltos and Benavides in 2019, in this research article we propose a new mixed-integer linear programming model to solve the university course timetabling problem. We approach the case of the Computing and Telecommunications School of a private university in Ecuador. The model is novel because it simultaneously incorporates the assignment of classrooms and the scheduling of the subjects that will be taught during the semester. Using the AIMMS modeler, we got a feasible solution in less than 20 seconds, while optimizing several quality indicators set by the academic coordination. The results highlight the importance of using Operations Research as a support tool in decision-making, especially in combinatorial problems that take weeks to solve manually.